2017
DOI: 10.3844/ojbsci.2017.7.17
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and Growth Performance of <i>Shorea macrophylla</i> (de Vriese) after Enrichment Planting for Reforestation Purpose at Sarawak, Malaysia

Abstract: Reforestation may offer one means of mitigating the processes of forest land degradation and is indispensable in an effort to conserve forest biological diversity in the tropics. Thus, a preliminary assessment was conducted in order to evaluate the survivorship and growth performance of Shorea macrophylla (de Vriese) after enrichment planting for reforestation purpose in Sarawak, Malaysia. This study was conducted at reforestation sites located at Sampadi Forest Reserve, Sarawak, Malaysia where indigenous Dipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 11 publications
2
31
1
1
Order By: Relevance
“…A brief summary of the relationship between PC1 score, SFI, SEF, and tree growth parameters (diameter at breast height (DBH) and height) and percentage of survival was shown in Table 4. Notwithstanding, to predict the best indicator for estimating soil fertility and site quality in relation to survivorship and growth performance of planted Shorea macrophylla after enrichment planting, the values of soil available phosphorus content at the rehabilitation sites at both surface and subsurface soil depths were correlated with tree growth parameters (diameter at breast height (DBH) and height) and survival from our previous study [18]. The results indicated that there was a strong relationship between the soil available phosphorus and tree growth parameters: diameter at breast height, height, and percentage of survival as shown in Figure 6.…”
Section: Relationship Between Soil Fertility and Growth Performance Omentioning
confidence: 99%
See 4 more Smart Citations
“…A brief summary of the relationship between PC1 score, SFI, SEF, and tree growth parameters (diameter at breast height (DBH) and height) and percentage of survival was shown in Table 4. Notwithstanding, to predict the best indicator for estimating soil fertility and site quality in relation to survivorship and growth performance of planted Shorea macrophylla after enrichment planting, the values of soil available phosphorus content at the rehabilitation sites at both surface and subsurface soil depths were correlated with tree growth parameters (diameter at breast height (DBH) and height) and survival from our previous study [18]. The results indicated that there was a strong relationship between the soil available phosphorus and tree growth parameters: diameter at breast height, height, and percentage of survival as shown in Figure 6.…”
Section: Relationship Between Soil Fertility and Growth Performance Omentioning
confidence: 99%
“…Nonetheless, in order to determine the applicability of these indices for estimating soil fertility and site quality in relation to survivorship and growth performance of planted Shorea macrophylla after enrichment planting, the values of the PC1 score, SFI, and SEF at both surface and subsurface soil depths were further correlated with the tree growth parameters (diameter at breast height (DBH) and height) and survival of the planted Shorea macrophylla trees from our previous study [18]. The results revealed positive and moderate correlations between the PC1 score and diameter at breast height (DBH) and survival percentage at surface soils ( = 0.546 * * , P < 0.01 and = 0.477 * , P < 0.05, resp.)…”
Section: Relationship Between Soil Fertility and Growth Performance Omentioning
confidence: 99%
See 3 more Smart Citations